Antioxidant and ROS Inhibitory Activities of Heterocyclic 2-Aryl-4(3H)-quinazolinone Derivatives - Perveen, Shahida; Saad, Syed M.; Khan, Khalid Mohammed; Choudhary, Muhammad Iqbal (Letters in Drug Design & Discovery, 2021)
Background: Antioxidants are small molecules that prevent or delay the process of oxidations caused by highly reactive free radicals. These molecules are known for their ability to protect various cellular architecture and other biomolecules from oxidative stress and free radicals. Thus, antioxidants play a key role in the prevention of oxidative damages caused by highly reactive free radicals. Methods: In the present study, a series of previously synthesized heterocyclic 2-aryl-4(3H)- quinazolinone derivatives 1-25 were screened for antioxidant activity by employing in vitro DPPH and superoxide anion radical scavenging activities. ROS inhibitory activities were also evaluated by serum-opsonized zymosan activated whole blood phagocytes and isolated neutrophils. Cytotoxicity studies were carried out by employing an MTT assay against the 3T3 cell line. Results: Most of the 2-aryl-4(3H)-quinazolinone derivatives showed potent antioxidant activities in superoxide anion radical scavenging assay with IC50 value ranging between 0.57 μM - 48.93 μM, as compared to positive control quercetin dihydrate (IC50 = 94.1 ± 1.1 μM ). Compounds 5, 6, and 14 showed excellent activity in DPPH assay. Compounds 5-8, 12-15, 17, and 20 showed promising activities in the ROS inhibition assay. All compounds were found to be non-cytotoxic against the 3T3 cell line. Structure antioxidant activity has been established. Conclusion: It can be concluded that most of the heterocyclic 2-aryl-4(3H)-quinazolinone derivatives 1-25 are identified as promising antioxidant agents that are capable of fighting against free radicals and oxidative stress. Thus, they can serve as a lead towards treating oxidative stress and related pathologies.
Keywords: oxidative stress